2009
DOI: 10.1371/journal.pone.0004551
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Treatment Responses to Artesunate-Mefloquine on the Northwestern Border of Thailand during 13 Years of Continuous Deployment

Abstract: BackgroundArtemisinin combination treatments (ACT) are recommended as first line treatment for falciparum malaria throughout the malaria affected world. We reviewed the efficacy of a 3-day regimen of mefloquine and artesunate regimen (MAS3), over a 13 year period of continuous deployment as first-line treatment in camps for displaced persons and in clinics for migrant population along the Thai-Myanmar border.Methods and Findings3,264 patients were enrolled in prospective treatment trials between 1995 and 2007 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
195
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(206 citation statements)
references
References 28 publications
9
195
2
Order By: Relevance
“…32,34,[37][38][39][40][41] However, in certain areas, for example, along Cambodia-Thailand and northwestern border of Thailand, the efficacy of AMQ is declining primarily because of resistance to MQ. 42,43 Recently, artemisinin resistance has been reported in Cambodia. 44 Thus, close monitoring will be needed with the use of AMQ in those areas of West Africa where reduced in vitro susceptibility has been reported to MQ and artemisinin 13 and where patients are more likely to take the artesunate and leave the MQ component or the possibility of providers selling one drug to reduce costs in co-packaging now available in many endemic areas of West Africa.…”
Section: Discussionmentioning
confidence: 99%
“…32,34,[37][38][39][40][41] However, in certain areas, for example, along Cambodia-Thailand and northwestern border of Thailand, the efficacy of AMQ is declining primarily because of resistance to MQ. 42,43 Recently, artemisinin resistance has been reported in Cambodia. 44 Thus, close monitoring will be needed with the use of AMQ in those areas of West Africa where reduced in vitro susceptibility has been reported to MQ and artemisinin 13 and where patients are more likely to take the artesunate and leave the MQ component or the possibility of providers selling one drug to reduce costs in co-packaging now available in many endemic areas of West Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The two most powerful predictors of parasite clearance time were age (proxy for acquired immunity in this population) and asexual parasitemia at the time of enrollment. [15][16][17][18] Based on previous studies, [16][17][18][19] the following variables were also included in the initial models as potential confounders of parasite clearance: sex, mixed parasite infection, and hemoglobin, gametocyte density, gametocyte carriage, and fever at the time of enrollment. All statistical analyses were done with Stata version 11.0 (StataCorp., College Station, TX).…”
Section: Methodsmentioning
confidence: 99%
“…An intensive study conducted at a different site in western Cambodia in 2007-08 reported a significant delay in parasite clearance time following treatment with artesunate monotherapy and with ACT (artesunate + mefloquine), as compared with parasite clearance times observed in eastern Thailand (87). Of note, the reduction of therapeutic responses to ACT has not been geographically confined to western Cambodia but also observed in southern Cambodia (88), on the ThailandMyanmar border (89), and in Yunnan in China (90). In particular, the proportion of patients showing a very slow rate of parasite clearance rapidly increased from 0.6z in 2001 to 20z in 2010 on the northwestern border of Thailand (91).…”
Section: -2 Actsmentioning
confidence: 99%